P31 Travel insurance in achd patients: Do they declare their condition?. (2nd March 2016) - Pickup, Luke; Bowater, Sarah; Thorne, Sara; Clift, Paul; Hudsmith, Lucy.
Abstract : Introduction: Adult congenital heart disease (ACHD) patients are encouraged to live as active a life as possible. For most patients, international travel is realistic. However, adequate travel insurance is critical but may be difficult to obtain. Awareness of the need for disclosure of relevant cardiac conditions when obtaining insurance has not been studied amongst these patients. Method: Anonymised questionnaires were distributed to patients at the ACHD clinics of a large quaternary ACHD specialist centre over a 2 week period. Responses were then collated and descriptive statistics used to analyse patients' responses. Results: 107 patients completed the questionnaire 55% male, 45% female, with 92% of patients being aged between 18–54. 66% had been on holiday within the last 12 months, 51% of whom went to Europe, 28% remained within the UK and the remaining 21% travelled outside of Europe. Of the total number who travelled outside of the UK, 86% had travel insurance. Almost a quarter (23%) did not declare that they had a pre-existing heart condition. Of those that did declare their condition 31% reported that it incurred a premium charge. Of those specifically travelling in Europe 71% stated that they used an EHIC card. 90% of respondents felt that insurance had not been fully addressed in the ACHD clinic, however only 10% stated that they had been rejected for a travel insurance application during their lifetime. Conclusion: This study shows that while the majority of patients seen in the ACHD clinic are using travel insurance, a significant percentage are not declaring their pre-existing heart conditions, which may render it invalid. Most patients feel that the need for adequate insurance has never been discussed in clinic. Appropriate counselling is essential to maximise patients' opportunities for travel, whilst ensuring adequate access to healthcare should problems arise. We recommend the availability of Sommerville Foundation Travel Insurance Leaflets in all ACHD clinics.